THE MODERATING ROLE OF AGE IN THE INFLUENCE OF HEALTH CONSCIOUSNESS AND PRICE PERCEPTION ON PURCHASE INTENTION OF ORGANIC FOOD - Ni Putu Delia Nandita; Ni Wayan Sri Suprapti (Adisam Publisher, 2025)
In response to growing environmental concerns and increasing awareness of sustainable consumption, organic food has emerged as a promising alternative to conventional products. This study investigates the influence of health consciousness and price perception on the purchase intention of organic food, with age as a moderating variable. Grounded in the Theory of Planned Behavior (TPB), this research employs a quantitative, causal-associative approach using a sample of 122 organic food consumers in Badung Regency, Bali—an area characterized by high purchasing power and demographic diversity. Data were collected through structured questionnaires and analyzed using multiple regression and Moderated Regression Analysis (MRA). The findings reveal that both health consciousness and price perception have a positive and significant effect on consumers’ purchase intention toward organic food. However, age does not moderate the relationship between health consciousness and purchase intention, nor does it moderate the effect of price perception on purchase intention. These results suggest that regardless of age, consumers are increasingly motivated to choose organic food when they perceive it as beneficial to their health and reasonably priced. The study highlights the potential for expanding the organic food market beyond demographic boundaries and provides insights for marketers and policymakers to design inclusive strategies that promote healthy and sustainable food choices.